Comparison between two different antibiotic regimes (2 grams stat then 1 gram 4 hourly ampicillin versus 1 gram stat then 500 mg 6 hourly of ampicillin) as antibiotic prophylaxis of maternal and neonatal sepsis in prom ≥18 hours prospective randomised controlled trial in Hospital Sultan Ismail, Johor Bahru, Johor - Yayanto, Nor Hidayah (2016)
Introduction: Pre-labour rupture of membranes is a common clinical problem with the predominant risk to the fetus is ascending infection. The risks to the mother are of uterine infection, via either chorioamnionitis and postpartum endometritis. Ampicillin group antibiotic is currently used as prophylaxis. Across the region, many antibiotic regime and dosage is recommended. Several studies showed conflicting outcome in search for optimal dosage. Objective: The aim of this study is to evaluate maternal and fetal outcome of two different regimes of Ampicillin dosage for antibiotic prophylaxis. Patient and Methods: A total of 292 patients were recruited in this study. Patients with term uneventful antenatal whom demonstrated PROM more than 18 hours were randomized into two different Ampicillin dosage regimes; a) 2 grams stat and 1 gram 4 hourly, b) 1 gram stat and 500 mg 6 hourly. Maternal outcome in term of duration of PROM, prostin insertion, level of WCC, temperature of 380C, dosage of antibiotic given prior to delivery, numbers of vaginal examinations, maternal chorioamnionitis and incident of postpartum endometritis were recorded. Fetal outcome measured include Apgar score at 1 minute, Apgar score at 5 minutes, NICU admission, early onset of neonatal sepsis and perinatal mortality. Both group were compared and t-test performed with significant level of p<0.05 is used. Results: A number of 146 patients in each armed fulfilled the inclusion criteria. There were no cases of postpartum endometritis and perinatal mortality recorded. Majority of patients delivered vaginally (88% in 2 gram groups, 99% in 1 gram group) followed by LSCS (23.35 in 2 grams group, 19.2% in 1 gram group). There were three cases of chorioamnionitis in 2 grams group (2.1%) and two cases (1.4%) in 1 gram group. Apgar score at 1 minute showed significant difference between two group with a number of nine cases (6.2%) less than 7 in 2 grams group and six cases (4.2%) in 1 gram group (p=0.049). There were 5 babies diagnosed as early onset of neonatal sepsis in 2 grams group (3.4%) and 3 babies in 1 gram group (2.1%). However, there were no significant different between two group Ampicillin regimes in relation to duration of PROM, prostin insertion, level of WCC, temperature of 380C, dosage of antibiotic given prior to delivery, numbers of vaginal examinations, Apgar score at 5 minutes, NICU admission and early onset of neonatal sepsis. Conclusion: Data from this study showed that there is no significant difference between the different dosage used as antibiotic prophylaxis for PROM patients with respect to maternal and fetal outcome (short and medium term outcome).